Changing Dynamics of Politics in Nepal: How Do Women Fear Party Politics? - Dahal, Kabita (Journal of Political Science, 2025)
Democracy is a political system that requires the participation of all citizens in the political process, including women in leadership roles. Successful democratization depends on ensuring women's full engagement in politics. This study investigates the apprehensions and systemic barriers that impede women’s political participation in Nepal. This study used a swift questionnaire survey combined with a Likert scale analysis to examine the perceptions of 156 women from diverse socio-economic backgrounds regarding both established and emerging political parties. The findings highlight that, despite feminist rhetoric from some parties, women's participation is significantly undermined because of concerns about harassment, political violence, and the potential for community reprisal. This resistance stems from deep-seated historical, social, and structural factors, leading to the marginalization of women. Notably, women from the informal sector and younger women reported higher levels of fear. In contrast, emerging parties were perceived as more responsive to women's concerns. This research emphasizes the urgent need for a secure and inclusive political environment that supports non-violent and meaningful representation of women. To achieve this, a concerted effort is required to address systemic barriers and patriarchal norms; develop gender-sensitive policies that empower women politically; and ultimately facilitate gender equity and a more inclusive, fair, and genuinely representative democracy in Nepal.